Removal of Molybdenum from Contaminated Groundwater Using Carbide-Derived Carbon - Yehia Manawi (14152704) (2022)
In the present work, the removal of Mo from aqueous solutions and real groundwater by using the novel high-surface-area adsorbent carbide-derived carbon (CDC) was performed. The adsorbent was characterized using X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), Brunauer, Emmett, and Teller (BET) surface area analysis, and Fourier-transform infrared spectroscopy (FTIR). The effect of the operational parameters (contact time, CDC loading, Mo concentration, and pH) on the adsorptive performance of the sorbent in the batch adsorption mode was studied. The experimental work revealed that the adsorption of Mo onto CDC is a very fast process and provides 99% Mo removal in less than 30 min. The adsorption process was pH-dependent, achieving the maximum adsorptive removal at a pH range of 3–5. The highest adsorption capacity corresponded to 16.24 mg/g at a Mo concentration of 10 ppm, adsorbent loading of 0.6 g/L, and pH 3. Four models were used to analyze the adsorption isotherms of Mo onto CDC, which were Freundlich, Langmuir, Temkin, and Sips. The obtained adsorption results were also processed using four adsorption kinetic models: intra-particle diffusion, Elovich, second-order, and pseudo-first-order. The adsorption of Mo onto CDC was found to fit the Freundlich isotherm model, as confirmed by the highest R2 values (0.9118) and lowest SSE (0.4777), indicating the heterogeneous multilayer adsorption of Mo onto CDC. Likewise, the experimental adsorption data were found to be more consistent with the pseudo-second-order model. The main adsorption mechanisms contributing to Mo adsorption were found to be electrostatic interactions and ligand–ligand exchange, in addition to surface complexation or ion exchange between Mo ions and oxygen-containing groups on the CDC’s surface. Moreover, the removal efficiency under acidic conditions (pH: 3) was found to be stable and high (>99%), regardless of the Mo concentration (0.5–10 ppm) due to the characteristic PZC corresponding to CDC (pH 9.9). A performance test of the CDC using both real groundwater and GW spiked with 570 µg/L Mo showed an almost complete removal of Mo from GW. The regeneration tests confirmed that adsorbed Mo can be recovered from CDC by pH adjustment and the regenerated CDC can be reused. Other Information Published in: Water License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/w15010049